Reducing Student Absenteeism in the Early Grades by Targeting Parental Beliefs. (December 2018) - Robinson, Carly D.; Lee, Monica G.; Dearing, Eric; Rogers, Todd
Attendance in kindergarten and elementary school robustly predicts student outcomes. Despite this well-documented association, there is little experimental research on how to reduce absenteeism in the early grades. This paper presents results from a randomized field experiment in 10 school districts evaluating the impact of a low-cost, parent-focused intervention on student attendance in grades K–5. The intervention targeted commonly held parental misbeliefs undervaluing the importance of regular K–5 attendance as well as the number of school days their child had missed. The intervention decreased chronic absenteeism by 15%. This study presents the first experimental evidence on how to improve student attendance in grades K–5 at scale and has implications for increasing parental involvement in education.